Development of Microstructural and Morphological Cortical Profiles in the Neonatal Brain - Fenchel, Daphna; Dimitrova, Ralica; Seidlitz, Jakob; Robinson, Emma C.; Batalle, Dafnis; Hutter, Jana; Christiaens, Daan; Pietsch, Maximilian; Brandon, Jakki; Hughes, Emer J.; Allsop, Joanna; O'Keeffe, Camilla; et al. (Cerebral Cortex, 2020)
Interruptions to neurodevelopment during the perinatal period may have long-lasting consequences. However, to be able to investigate deviations in the foundation of proper connectivity and functional circuits, we need a measure of how this architecture evolves in the typically developing brain. To this end, in a cohort of 241 term-born infants, we used magnetic resonance imaging to estimate cortical profiles based on morphometry and microstructure over the perinatal period (37-44 weeks postmenstrual age, PMA). Using the covariance of these profiles as a measure of inter-areal network similarity (morphometric similarity networks; MSN), we clustered these networks into distinct modules. The resulting modules were consistent and symmetric, and corresponded to known functional distinctions, including sensory-motor, limbic, and association regions, and were spatially mapped onto known cytoarchitectonic tissue classes. Posterior regions became more morphometrically similar with increasing age, while peri-cingulate and medial temporal regions became more dissimilar. Network strength was associated with age: Within-network similarity increased over age suggesting emerging network distinction. These changes in cortical network architecture over an 8-week period are consistent with, and likely underpin, the highly dynamic processes occurring during this critical period. The resulting cortical profiles might provide normative reference to investigate atypical early brain development.
CRIS-Team Scopus Importer:2023-03-08
Keywords: developing brain; morphometric similarity networks; multimodal MRI; perinatal; structural covariance